ANALYSIS OF STUDENT ERRORS IN SOLVING QUESTIONS ON A SYSTEM OF LINEAR EQUATIONS WITH TWO VARIABLES IN CLASS VIII SMP NEGERI 2 SOMAMBAWA SCHOOL YEAR 2022/2023 - Hulu, Lukas Jaya (Universitas Nias Raya, 2023)
This research is motivated by the existence of errors that students often make in solving mathematics problems. This research aims to describe students' errors in solving systems of two-variable linear equations. The subjects in this research were 24 students in class VIII of SMP Negeri 2 Somambawa for the 2022/2023 academic year. The data was analyzed using steps, namely data reduction, data presentation and drawing conclusions. The research data collection techniques used were tests and interviews. The results of the research show that students still make mistakes in solving problems on systems of linear equations in two variables. This results in students not being able to identify known data and the data asked for in the question. Students do not master mathematical calculation operations so they often make mathematical calculation errors. Apart from that, this error is also caused by students' lack of accuracy when carrying out mathematical calculations. So it was concluded that these errors included errors in organizing data for 13 students with a percentage of 54%, procedural errors and errors for 15 students with a percentage of 62%, and errors in drawing conclusions for 18 students with a percentage of 75%. Researchers suggest that mathematics teachers should provide students with more frequent exercises in solving systems of linear equations in two variables, especially in multiplication and subtraction operations, and division that is not divisible.